Craniometric measurement by jug handle view: An aid for gender determination - Sunira Chandra; Neha Chaturvedi; Kunal Sah; Shruti Sinha; Ali Hamza (Wolters Kluwer Medknow Publications, 2018)
Introduction: Dental identification can be done on the basis of "sexual dimorphism," which refers to the differences in size, stature and appearance of males and females. The most reliable bony structures for sex determinations are pelvis and skull. Zygomatic arch and vault area as being part of skull can be considered most reliable and accurate for their objectivity and reproducibility. Among the various skull radiographs, jug handle radiograph provides the best view of zygomatic arches and vault area. Hence the present study has been undertaken to measure bizygomatic and intervault distance on the jug handle radiograph for gender determination. Aim and Objectives:(i) To assess the efficacy and reliability of craniometric measurement using bizygomatic distance for gender determination. (ii) To assess the efficacy and reliability of craniometric measurement using intervault distance for gender determination. (iii) To determine the most appropriate and reliable craniometric method for gender determination among bizygomatic and intervault distance. Methodology: Sixty individuals (30 males and 30 females) between age group of 18 to 25 years were included in the study. Jug handle radiographs were taken under standardized manner. Bizygomatic and inter vault distances were measured, and the results obtained were later subjected to statistical evaluation (independent Student's t-test). Result: The average bizygomatic distance of male was found to be 72.594 and for female was 65.3583, and intervault distance for male was 63.8693 and for female were 59.664, which was found to be statistically significant. Conclusion: It was observed that males have more bizygomatic distance and intervault distance when compared to females. Also, bizygomatic distance gave better result as compare to intervault distance. Thus, based on the observations from the present study we can conclude that craniometric measurement can be considered as a reliable tool for gender determination.